2021
DOI: 10.3390/ma15010146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasonic-Assisted Casting on Hot Deformation Mechanism and Microstructure of 35CrMo Steel Ingot

Abstract: Hot compression tests were performed with strain rates (0.01–10 s−1) and temperatures (850–1150 °C). The power law relationship between the critical stress and critical strain and Zener–Hollomon parameters was determined by θ-σ curves. Microstructure was investigated by electron backscattered diffraction. The results showed that the flow behavior and microstructure of 35CrMo steel was affected by ultrasonic-assisted casting. The activation energy of non-ultrasonic and ultrasonic-assisted 35CrMo steel were 410 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…∑3 n ( n = 1, 2, 3) boundary, as a special grain boundary, can improve the mechanical properties of the alloy and has a significant effect on the microstructure of the material. [ 18 ] Furthermore, research has found that annealing twins can reduce the grain boundary energy and increase the grain boundary migration ability, playing a crucial role in the DRX process. In contrast, thermal processing promotes the interaction and regeneration between ∑3 and its variants (∑9 and ∑27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…∑3 n ( n = 1, 2, 3) boundary, as a special grain boundary, can improve the mechanical properties of the alloy and has a significant effect on the microstructure of the material. [ 18 ] Furthermore, research has found that annealing twins can reduce the grain boundary energy and increase the grain boundary migration ability, playing a crucial role in the DRX process. In contrast, thermal processing promotes the interaction and regeneration between ∑3 and its variants (∑9 and ∑27).…”
Section: Resultsmentioning
confidence: 99%
“…[15,17] CDRX mainly occurs inside the grain, continuously absorbing dislocations through progressive rotation of subgrains to increase the misorientation at subgrain boundaries, thereby forming DRX grains. [18,19] In the study of DRX, Zhang et al [20] studied the thermal deformation behavior of HIPed FGH96 superalloy and found that DDRX is the main nucleation mechanism and CDRX is the auxiliary mechanism in the DRX process. Wang et al [21] investigated the DRX mechanism of Inconel 740 superalloy and noted that DDRX and CDRX occur simultaneously during thermal deformation, while CDRX behavior is not active.…”
Section: Introductionmentioning
confidence: 99%